Effect of an Early Nutritional Supplement on Broiler Performance - Henderson, S.N.; Henderson, S.N.; Vicente, J.L.; Pixley, C.M.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2008)
Chicks are commonly held for up to 72 h from the time of actual hatch to placement under commercial industry practices. Delaying access to feed and water has been documented to increase susceptibility to pathogens and weight loss, leading to poorly starting flocks with reduced weight gains. Seven experiments were conducted to compare the use of EarlyBird™ (EB; Sigrah-Zellet, LLC.) to no supplementation (NS) in chick boxes when chicks were held for a 24 h simulated shipping period. In each experiment, broilers were obtained from a commercial hatchery, neck tagged, individually weighed, and randomly placed in boxes of 100 chicks. Treated chicks received 2 g/chick of EB. Following 24 h, chicks were individually weighed and placed with feed and water ad libitum. In all experiments, chicks that received EB during simulated shipping experienced significantly less body weight loss during the 24 holding period (p<0.05) and were significantly heavier at 7 d. At slaughter, EB treated broilers were 58 g heavier than the controls. The results are consistent with earlier reports indicating that the dependence of chicks on residual yolk sac during the first few days post hatch limits the growth potential of modern broilers. Early feeding can not only impact the general well being of the chick but also can have significant effects on early growth, leading to increased weight gains that persist through broiler production.